The influence of surfactant/co-surfactant hydrophilic-lipophilic balance on the formation of limonene-based microemulsion as vitamin C carrier - Ramli S.,; Chyi, K.T.; Zainuddin N.,; Mokhtar W.N.A.W.,; Abdul Rahman I., (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research was conducted to produce a limonene-based microemulsion system as vitamin C carrier. The microemulsion was produced using limonene as the oil phase, tween20 and tween80 as surfactants while propylene glycol, polyethylene glycol 400 and glycerol as co-surfactants. Pseudo-ternary phase diagrams were constructed to determine the microemulsion area by using the water titration method at 25°C. The effect of hydrophilic-lipophilic balance (HLB) value of the mixture of S/CoS on the formation of limonene-based microemulsion was studied. The HLB value calculated for the mixture of tween20/propylene glycol in the different ratio was between 10.1 and 13.4. From the experiment, the preparation of limonene-based microemulsion system with tween20/propylene glycol was able to provide large and high stability of microemulsion region on ternary phase diagram (23.6%) while higher HLB value resulted in larger microemulsion area in ternary phase diagrams. The sole formulation with propylene glycol was further selected to carry out the physicochemical characterization of system’s stability, particle size and electrical conductivity. All microemulsion systems showed good stability for four weeks at temperature of 4, 25 and 40°C without any phase change and separation. Particle size characterization results elucidated that all microemulsion systems consisted particle size between 20 and 100 nm. The study of electrical conductivity showed that water-in-oil microemulsion was formed from 5-45% wt. of water whereas bicontinuous microemulsion was formed from 50-90% wt. of water content. Overall, the result showed that microemulsion tween20/propylene glycol/limonene/water was potential as a carrier system of vitamin C.